Comparative evaluation of life cycle impact assessment software tools through a wind turbine case study. (February 2015) - Martínez, E.; Blanco, J.; Jiménez, E.; Saenz-Díez, J.C.; Sanz, F.
Abstract: This paper seeks to analyse the differences between environmental impact assessment software tools by examining the results that they give when applied to a multi-megawatt wind turbine. Seven different life cycle impact assessment software tools are compared: CML 2001, Eco-indicator 99, Ecopoints 97, EDIP, EPS 2000, IMPACT2002 and TRACI. In Acidification and Eutrophication two groups are found: one includes the results provided by CML, Ecopoints 97, EDIP, EPS and TRACI and the other those of Eco-indicator 99 and Impact2002. In Abiotic Depletion all the results are similar except those of the EPS method, which gives negative figures. Likewise in Ozone Layer Depletion the results provided by Ecopoints 97 differ from the rest. In Human Toxicity and Ecotoxicity markedly different results are obtained by each of the LCIAs studied. In some categories major differences are found between the results provided by the 7 LCIAs examined. Which of the impact assessment software tools currently available in LCA software is chosen is therefore a critical issue. The results provided by the different software tools are not always similar, and this needs to be realised and taken into account when using the resulting data in decision-making processes. Highlights: Differences between environmental impact assessment methods. In Acidification and Eutrophication two groups are found. In Abiotic Depletion all the results are similar except those of the EPS method. In Ozone Layer Depletion the results provided by Ecopoints 97 differ from the rest.